Grundtvigs vej til Saxo - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 2015)
This article documents Grundtvig’s path to the works of Saxo Grammaticusfrom around 1787, when he was taught to read by his strongwilledmother, and until departure from Saxo after completing his translationof Saxo’s chronicle in 1823. An overview of this period focuses onthe significant dates, book titles, and other points of interest that mark hisinterest in the medieval clerical scribe’s work. Attention then turns to thefact that, after 1823, Grundtvig never seriously returned to study of Saxo’sideas, nor did he ever try to reproduce his silver age Roman style in the Danish language. For a very short while, Grundtvig thought about butnever followed through on a continuation of a history of Denmark fromwhere Saxo stopped (viz. in 1186). Though Grundtvig’s preoccupationwith Saxo lasted for the rest of his life, he preferred the Icelandic tongueinstead of Latin and believed that Norse mythology was a more fertilefield than Latin for discoveries about the national history of the Danes.The present survey of these key points in how Grundtvig viewed andevaluated Saxo also supplements previous scholarly treatments of stylisticlinguisticanalyses of Grundtvig’s youth translation of Saxo.